Swiss-wide multicentre evaluation and prediction of core outcomes in arthroscopic rotator cuff repair: protocol for the ARCR_Pred cohort study. Issue 4 (22nd April 2021) - Audigé, Laurent; Bucher, Heiner C C; Aghlmandi, Soheila; Stojanov, Thomas; Schwappach, David; Hunziker, Sabina; Candrian, Christian; Cunningham, Gregory; Durchholz, Holger; Eid, Karim; Flury, Matthias; Jost, Bernhard; et al.
Abstract : Introduction: In the field of arthroscopic rotator cuff repair (ARCR), reporting standards of published studies differ dramatically, notably concerning adverse events (AEs). In addition, prognostic studies are overall methodologically poor, based on small data sets and explore only limited numbers of influencing factors. We aim to develop prognostic models for individual ARCR patients, primarily for the patient-reported assessment of shoulder function (Oxford Shoulder Score (OSS)) and the occurrence of shoulder stiffness 6 months after surgery. We also aim to evaluate the use of a consensus core event set (CES) for AEs and validate a severity classification for these events, considering the patient's perspective. Methods and analysis: A cohort of 970 primary ARCR patients will be prospectively documented from several Swiss and German orthopaedic clinics up to 24 months postoperatively. Patient clinical examinations at 6 and 12 months will include shoulder range of motion and strength (Constant Score). Tendon repair integrity status will be assessed by ultrasound at 12 months. Patient-reported questionnaires at 6, 12 and 24 months will determine functional scores (subjective shoulder value, OSS), anxiety and depression scores, working status, sports activities, and quality of life (European Quality of Life 5 Dimensions 5 Level questionnaire). AEs will be documented according to a CES. Prognostic models will be developed using an internationally supported regression methodology. Multiple prognostic factors, including patient baseline demographics, psychological, socioeconomic and clinical factors, rotator cuff integrity, concomitant local findings, and (post)operative management factors, will be investigated. Ethics and dissemination: This project contributes to the development of personalised risk predictions for supporting the surgical decision process in ARCR. The consensus CES may become an international reference for the reporting of complications in clinical studies and registries. Ethical approval was obtained on 1 April 2020 from the lead ethics committee (EKNZ, Basel, Switzerland; ID: 2019-02076). All participants will provide informed written consent before enrolment in the study. Trial registration number: NCT04321005 . Protocol version: Version 2 (13 December 2019).